Assessing alexithymia across negative and positive emotions: Psychometric properties of the Polish version of the Perth Alexithymia Questionnaire - Larionow, Paweł; Preece, David A.; Mudło-Głagolska, Karolina (Frontiers in Psychiatry, 2022)
The Perth Alexithymia Questionnaire (PAQ) is a 24-item self-report measure of alexithymia. Originally developed in English, it was designed to try to enable more comprehensive (i.e., facet-level and valence-specific) alexithymia assessments. This study aimed to introduce and validate a Polish version of the PAQ. Our sample were 1,008 people (69.44% females, 30.06% males and 0.50% non-binary) aged 18–78 (M = 29.69, SD = 14.15) from the general community. The PAQ's factor structure was verified with confirmatory factor analysis, and convergent and divergent validity were assessed via relationships with other measures of alexithymia and mental health symptoms. Our results indicated strong factorial validity, conforming to the intended subscale structure. As expected, all PAQ subscales correlated in expected directions with another established alexithymia measure, and markers of depression, anxiety, and stress symptoms. The PAQ showed good discriminant validity in terms of measuring an alexithymia construct that was separable from people's current level of distress. Test-retest and internal consistency reliabilities were also good. Overall, the Polish PAQ therefore appears to have strong psychometric properties. Our findings add to a growing body of literature supporting the validity of the PAQ, and the multidimensional nature of the alexithymia construct, across different nations and languages.